Sympathetic neuropathology is revealed in muscles affected by amyotrophic lateral sclerosis - Mazzaro, Antonio; Vita, Veronica; Ronfini, Marco; Casola, Irene; Klein, Arianna; Dobrowolny, Gabriella; Sorarù, Gianni; Musarò, Antonio; Mongillo, Marco; Zaglia, Tania (Frontiers in Physiology, 2023)
Rationale: The anatomical substrate of skeletal muscle autonomic innervation has been described many decades ago but remained underappreciated since. As such, the structural and functional features of muscle sympathetic innervation are largely undetermined in both physiology and pathology, mainly due to methodologic limitations in the histopathologic analysis of the small neuronal fibers in tissue samples. Amyotrophic Lateral Sclerosis (ALS) is a fatal neuromuscular disease which mainly targets motor neurons and, despite autonomic symptoms occur in a significant fraction of patients, peripheral sympathetic neurons (SNs) are generally considered unaffected and, as such, poorly studied. Purpose: We here compared sympathetic innervation of normal and ALS muscles, through structural analysis of the sympathetic network in human and murine tissue samples. Methods and Results: We firstly refined tissue processing to circumvent methodologic limitations interfering with detection of muscle sympathetic innervation. The optimized ‘Neuro Detection Protocol’ (NDP) was validated in human muscle biopsies, demonstrating that SNs innervate, at high density, both blood vessels and skeletal myofibers, independently from the fiber metabolic type. Subsequently, NDP was exploited to analyze sympathetic innervation in muscles from SOD1G93A mice, a preclinical ALS model. Our data shows that ALS murine muscles display SN denervation, which starts already at the early disease stage and worsens during ageing. SN degeneration was also observed in muscles of MLC/SOD1G93A mice, with muscle specific expression of the SOD1G93A mutant gene. Notably, similar alterations in SNs were observed in muscle biopsies from an ALS patient, carrying the SOD1G93A mutation. Conclusions: We set up a protocol for the analysis of murine and, more importantly, human muscle sympathetic innervation. Our results indicate that SNs are additional cell types compromised in ALS and suggests that dysfunctional SOD1G93A muscles impact on their sympathetic innervation.